m6A mRNA Methylation Was Associated With Gene Expression and Lipid Metabolism in Liver of Broilers Under Lipopolysaccharide Stimulation - Guo, Feng; Zhang, Yanhong; Ma, Jinyou; Yu, Yan; Wang, Qiuxia; Gao, Pei; Wang, Li; Xu, Zhiyong; Wei, Xiaobing; Jing, Mengna (Frontiers in Genetics, 2022)
Hepatic inflammation is always accompanied with abnormal lipid metabolism. Whether N6-methyladenosine (m6A) mRNA methylation affects irregular inflammatory lipid level is unclear. Here, the m6A modification patterns in chicken liver at the acute stage of LPS-stimulated inflammation and at the normal state were explored via m6A and RNA sequencing and bioinformatics analysis. A total of 7815 m6A peaks distributed in 5066 genes were identified in the normal chicken liver, and were mostly located in the CDS, 3’UTR region and around the stop codon. At 2 h after the LPS intraperitoneal injection, the m6A modification pattern changed, and showed 1200 different m6A peaks. The hyper- and hypo-m6A peaks were differentially located, with the former mostly located in the CDS region and the later in the 3’UTR and in the region near the stop codon. The hyper- or hypo methylated genes were enriched in different GO ontology and pathways. Co-analysis revealed a significantly positive relationship between the fold change of m6A methylation level and the relative fold change of mRNA expression. Moreover, protein and protein interaction analysis showed that genes with altered m6A methylation and mRNA expression levels were clustered in processes involved in lipid metabolism, immune response, DNA replication and protein ubiquitination. CD18 and SREBP-1 were the two hub genes clustered in the immune process and lipid metabolism, respectively. Hub gene AGPAT2 was suggested to link the immune response and lipid metabolism clusters in the PPI network. This study presented the first m6A map of broiler chicken liver at the acute stage of LPS induced inflammation. The findings may shed lights on the possible mechanisms of m6A-mediated lipid metabolism disorder in inflammation.